AngularJS Web Application Development Blueprints. - Rufus, Vinci (Packt Publishing, 2014)
If you are a web application developer interested in using AngularJS for a real-life project, then this book is for you. As a prerequisite, knowledge of JavaScript and HTML is expected, and a working knowledge of AngularJS is preferred.